Study on the correlation between microbial communities with physicochemical properties and flavor substances in the Xiasha round of cave-brewed sauce-flavor Baijiu - Ren, Tingting; Su, Wei; Mu, Yingchun; Qi, Qi; Zhang, Dangwei (Frontiers in Microbiology, 2023)
The main production areas of sauce-flavor Baijiu were concentrated in the Chishui River basin. Due to the particularity of sauce-flavor Baijiu technology, a large site of workshops needs to be built for brewing and storage. Therefore, the natural karst caves of Guizhou province have been gradually been used to manufacture the sauce-flavor Baijiu, which has to enriched the connotation of sauce-flavor Baijiu and saved valuable land resources. In this study, the fermentation grains in the seven stages during the Xiasha round of the cave brewed sauce-flavor Baijiu (CBSB) were detected using a combination of physicochemical analysis, Headspace solid-phase microextraction gas chromatography-mass detection, and Illumina HiSeq sequencing methods. The results showed Unspecified_Leuconostocaceae, Weissella, Unspecified_Bacillaceae, Saccharomycopsis, Thermomyces, and Unspecified_Phaffomycetaceae were the main bacterial and fungal genera in the stacking fermentation (SF). In the cellar fermentation (CF), the Lactobacillus, Unspecified_Lactobacillaceae, Thermoactinomyces, Saccharomycopsis, Unspecified_Phaffomycetaceae, and Wickerhamomyces were the main bacterial genera and the main fungal genera. Linear discriminant analysis Effect Size (LEfSe) identified 23 significantly different volatile metabolites in the fermentation process. Redundancy analysis was used to explore the correlation between dominant microorganisms and physicochemical properties while calculating the Pearson correlation coefficient revealing the correlation between dominant microorganisms and significantly different volatile flavor substances. On this basis, established a metabolic map of the dominant microbial genera. This study provides a theoretical basis for the production and quality control of sauce-flavor Baijiu brewed in natural karst caves and lays a foundation for studying the link between flavor formation and microorganisms.